The Problem of a Rational Consensus: J. Rawls versus J.-F. Lyotard - Vasiliauskaitė, Nida (Problemos, 2004)
The article deals with the problem of a rational consensus in contemporary political philosophy, aroused by postmodern critique of modern Reason. In this context two important ideas – an “Overlapping consensus” of John Rawls and “the Differend” of Jean-François Lyotard – are discussed, compared and criticized. Paradoxical implications produced by a common antifoundationalist approach are pointed out. An attempt is made to show that in both cases consensus or disensus are already presupposed in advance: the kind of the thesis depends upon suppositions about the nature of epistemic pluralism and its link with the political.
Keywords: Rawls; Lyotard; rationality; consensus; differend